2.5k views
5 votes
Which is the missing term? (10x - 4x^2)-(7x+ ? ) = 3x-6x^2

Which is the missing term? (10x - 4x^2)-(7x+ ? ) = 3x-6x^2-example-1
User Xrdty
by
5.7k points

2 Answers

4 votes

2x^2 because you do (-4x^2)-x=(-6x^2) and solve for x to get 2x^2.

User Lingviston
by
5.5k points
3 votes

Answer:

The missing term is -2x²

Explanation:

It is given that,

(10x - 4x² ) - (7x + ?) = 3x - 6x²

To find the missing term

Let 'M' be the missing term we can write the above equation,

(10x - 4x² ) - (7x + M) = 3x - 6x²

⇒ 10x - 4x² - 7x + M = 3x - 6x²

⇒ 10x - 7x - 4x² + M = 3x - 6x²

⇒ 3x - 4x² + M = 3x - 6x²

M = -6x² + 4x²

M = -2x²

User Baker
by
5.7k points